2008
DOI: 10.4067/s0717-95022008000400037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Nicotine on Rat Liver Stereology

Abstract: SUMMARY:Nicotine is the more abundant component in cigarette smoke. Because nicotine is first metabolized in the liver, our aim was to investigate the effects of nicotine on this organ by biochemical and stereological methods. Male Wistar rats were treated with oral nicotine (ON) diluted in drinking water during 32 days. The control group was treated with drinking water in the same period. Rats were sacrificed 24 hours after last day, the blood was collected and the liver was removed. Lipidogram was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
(89 reference statements)
2
13
0
1
Order By: Relevance
“…The chronic administration of nicotine also leads to deleterious effects in hepatic tissue. Adult Wistar rats treated daily for 10 days with 5 mg of nicotine in drinking water showed varied size of hepatocytes with different histoarchitecture; increase of fat drops in cytoplasm and reduction of hepatocyte number (Valenca et al, 2008). Liver lesions were also observed in pups of 10 days submitted to prenatal exposure to nicotine (4.3 ± 0.3 mg/kg/day at drinking water), demonstrating that during hepatic organogenesis, nicotine induced a hepatic focal necrosis in utero that persist for 10 days without reversion after nicotine withdrawal.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The chronic administration of nicotine also leads to deleterious effects in hepatic tissue. Adult Wistar rats treated daily for 10 days with 5 mg of nicotine in drinking water showed varied size of hepatocytes with different histoarchitecture; increase of fat drops in cytoplasm and reduction of hepatocyte number (Valenca et al, 2008). Liver lesions were also observed in pups of 10 days submitted to prenatal exposure to nicotine (4.3 ± 0.3 mg/kg/day at drinking water), demonstrating that during hepatic organogenesis, nicotine induced a hepatic focal necrosis in utero that persist for 10 days without reversion after nicotine withdrawal.…”
Section: Tablementioning
confidence: 99%
“…Thus, the NAFLD is correlated with decrease of antioxidant defenses (Conceição et al, 2013;Rolo et al, 2012;Videla et al, 2004). According to Valenca et al (2008), oral chronic nicotine exposure in adult rats is associated with impairment of lipid metabolism and microsteatosis. However, these authors did not investigate the oxidative status in this model.…”
Section: Introductionmentioning
confidence: 96%
“…The second method is a modification introduced by Scherle (1970) over 40 years ago. It has been used in mouse (Karbalay-Doust & Noorafshan, 2009) and rat liver (Aguila et al 2003;Souza-Mello et al 2007;Valenca et al 2008;Halici et al 2009a,b). In the Scherle's method the organ is also fully immersed in fluid (of known density), but now suspended by a thin thread (care must be taken so that the liver does not touch the side or bottom of the container) -because the density of the used fluid is typically 1 (e.g.…”
Section: Volumementioning
confidence: 99%
“…These methods are widely used in microscopic anatomy and development (Furrianca et al, 2008;Valenca et al, 2008;Vásquez & del Sol, 2009). Though the value of the delivered data is not reflected in the level of evidence that they provide, it cannot be concluded that studies that use stereology provide poor information.…”
Section: Discussionmentioning
confidence: 99%